(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Arka kalpana is a unique pharmaceutical preparation in Ayurveda in which the volatile oil and active principles of a drug are collected by the process of distillation using Arka yantra or any convenient modern distillation apparatus. Mukhapakahara arka is a formulation mentioned in Arka prakasha sapthama shataka as a Gandusha yoga to cure Mukhapaka. The ingredients of Mukhapakahara arka are Jatheepatra, Amruta, Draksha, Vasa, Darvi, Hareetaki, Vibheetaki and Amalaki. Based on the properties of the ingredients, the formulation possesses potent wound healing, anti- inflammatory properties and hence could be beneficial in conditions like Recurrent Aphthous Stomatitis. Being an Arka kalpana, Mukhapakahara arka has many advantages in terms of palatability, shelf life and user-friendly aspects. No previous works have been carried out on Mukhapakahara arka. In this study, Mukhapakahara arka was prepared and was subjected to organoleptic evaluation and physicochemical tests like determination of pH value, specific gravity and volatile matter. HPTLC profile of Mukhapakahara arka was also obtained which could be useful for further works.